Hack proofing your wireless network - Barnes, Christian; O'Farrell, Neal. (Rockland, Mass. : Syngress Pub. : Distributed by Publishers Group West in the U.S. & Jaguar Book Group in Canada, 2002)
The only way to stop a hacker is to think like one! Wireless technology is a new and rapidly growing field of concentration for network engineers and administrators. Innovative technology is now making the communication between computers a cordless affair. Wireless devices and networks are vulnerable to additional security risks because of their presence in the mobile environment. Hack Proofing Your Wireless Network is the only book written specifically for architects, engineers, and administrators responsible for securing their wireless networks. From making sense of the various acronyms (WAP, WEP, SSL, PKE, PKI, SSL, SSH, IPSEC) to the implementation of security policies, plans, and recovery protocols, this book will help users secure their wireless network before its security is compromised. The only way to stop a hacker is to think like one ... this book details the multiple ways a hacker can attack a wireless network - and then provides users with the knowledge they need to prevent said attacks. Uses forensic-based analysis to give the reader an insight into the mind of a hacker With the growth of wireless networks architects, engineers and administrators will need this book Up to the minute Web based support at www.solutions@syngress.com.
Includes index.
Keywords: Computer networks -- Security measures; Wireless communication systems -- Security measures; Wireless LANs -- Security measures; Electronic books